LANGUAGE TEACHERS’ DIFFICULTIES OF BOGOR-BEKASI-BANTEN IN CONDUCTING CLASSROOM ACTION RESEARCH - Defina Defina; Siti Aisah; Nur Qolbi (IAIN MADURA, 2018)
To improve students’ language skill, the teacher needs to find out what are the appropriate techniques in teaching to achieve particular goals. The teacher can research to get the solution. One kind of research that can be conducted is Classroom Action Research (CAR). However, teachers sometimes find difficulties in implement it. The aim of this research is to find out teachers’ difficulties in conducting CAR. This is qualitative research. The samples of the research are 22 teachers from 5 high schools in Bogor, Bekasi, and Serang (Banten). Data collecting technique is conducted through questionnaire and interview. The results of this research are 1) the teachers are lack of information on how to conduct CAR, 2) teachers do not have much time to spend hours in conducting research since they have to teach many classes, and 3) Research training or workshop for teachers are rarely being conducted at those six schools in Bogor, Bekasi, and Serang (Banten).